Arecoline aggravates acute ulcerative colitis in mice by affecting intestinal microbiota and serum metabolites - Zhao, Hu; Ding, Taohui; Chen, Yanglin; Yang, Wenbin; Rao, Jun; Liu, Dan; Yi, Bo (Frontiers in Immunology, 2023)
Arecoline is an alkaloid extracted from betel nut, which has various pharmacological effects. In the present study, we showed that arecoline aggravated experimental acute ulcerative colitis (UC) induced by dextran sodium sulfate (DSS) in mice. We measured body weight and colon length, evaluated disease activity index, colon pathology sections, and levels of colonic inflammatory factors. Arecoline exacerbated the clinical signs of UC and the colonic inflammatory response in mice.The results of 16S rRNA sequencing of fecal samples showed a significant decrease in the percentage of probiotic bacteria Ligilactobacillus, Limosilactobacillus and Lactobacillus and a significant increase in the percentage of conditionally pathogenic bacteria Odoribacter and Bacteroides after arecoline treatment. Serum untargeted metabolomics showed that arecoline intervention reduced the levels of ergothioneine, pentostatin, diadenosine tetraphosphate and other metabolites and modulated nicotinate and nicotinamide metabolism, metabolic pathways, glyoxylate and dicarboxylate metabolism, and other metabolic pathways of intestinal microorganisms. According to the combined microbial and metabolite analysis, arecoline influences metabolite levels by modulating the intestinal microbiota. In summary, it was found that arecoline treatment exacerbated colonic injury and intestinal inflammatory responses in UC mice, disrupted the host's intestinal flora, and affected changes in flora metabolites, thereby exacerbating the development of colonic inflammation.Therefore, the consumption of betel nut can be associated with the risk of aggravating UC.